WAYS OF GLOBAL ERADICATION OF POLIOMYELITIS IN CHILDREN IN UKRAINE - Pikul, Е.В.; Ilchenko, V.I.; Prilutskiy, K.Yu. (World of Medicine and Biology, 2016)
In connection with deterioration of epidemiological situation on poliomyelitis in the world before us the task is put: to not admit cases of sick rate on poliomyelitis, was well-timed to tap circulation of wild virus both in an environment and among children. Results of the analysis of statistical and literary data allow to correct actions of doctors in the decision of a question of the prevention of sick rate on poliomyelitis among children.
Keywords: poliomyelitis; children; prophylaxis